Alexander Hamilton papers - Hamilton, Alexander, 1757-1804.; First Church in Albany
Correspondence, speeches, writings, legal and financial records, printed matter, and other papers relating to Hamilton's personal life and public career, especially his service as an aide to George Washington during the Revolutionary War, his participation in the U.S. Continental Congress and the Constitutional Convention, his service as U.S. secretary of the treasury, his New York law practice, and his service as inspector general of the U.S. Army. Subjects include military affairs such as recruiting and organizing the army, supply logistics, and condition at the forts, especially in the West; economic issues such as public finance, creation of a national bank, establishment of a mint, development of manufacturing, and the Society for Establishing Useful Manufactures; U.S. relations with France and Great Britain; acceptance of the U.S. Constitution by the New York ratifying convention in 1788; legal cases before the New York Supreme Court; and the Hamilton, McLane, Schuyler, and Church families.
Correspondents include John Adams; Angelica Schuyler Church; Henry Clay; Elizabeth Schuyler Hamilton; John Francis Hamtramck; William Heth; John Jay; Thomas Jefferson; Rufus King; Marie Joseph Paul Yves Roch Gilbert du Motier, marquis de Lafayette; Henry Lee; Pierre Charles L'Enfant; James McHenry; James Monroe; Robert Morris; Timothy Pickering; Charles Cotesworth Pinckney; Nathan Rice; John J.U. Rivardi; Philip John Schuyler; Theodore Sedgwick; William Seton; William Stephens Smith; Friedrich Wilhelm Ludolf Gerhard Augustin, Baron von Steuben; Caleb Swan; Louis de Tousard; Robert Troup; Jeremiah Wadsworth; George Washington; James Wilkinson; and Oliver Wolcott.
Microfilm edition available, in part
Microfilm produced from originals in the Manuscript Division.
Delegate from New York to the U.S. Continental Congress, U.S. secretary of the treasury, U.S. army officer, statesman, and lawyer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Includes a photostat of marriage records listing Alexander Hamilton and Elizabeth Schuyler which was formerly cataloged separately under First Church of Albany Records.
Keywords: Adams, John, -- 1735-1826 -- Correspondence; Church, Angelica Schuyler, -- 1756-1815 -- Correspondence; Clay, Henry, -- 1777-1852 -- Correspondence; Hamilton, Elizabeth Schuyler, -- 1757-1854 -- Correspondence; Hamtramck, John Francis, -- 1756-1803 -- Correspondence; Heth, William, -- 1735-1808 -- Correspondence; Jay, John, -- 1745-1829 -- Correspondence; Jefferson, Thomas, -- 1743-1826 -- Correspondence; King, Rufus, -- 1755-1827 -- Correspondence; Lafayette, Marie Joseph Paul Yves Roch Gilbert du Motier, -- marquis de, -- 1757-1834 -- Correspondence; Lee, Henry, -- 1756-1818 -- Correspondence; L'Enfant, Pierre Charles, -- 1754-1825 -- Correspondence; McHenry, James, -- 1753-1816 -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Morris, Robert, -- 1734-1806 -- Correspondence; Pickering, Timothy, -- 1745-1829 -- Correspondence; Pinckney, Charles Cotesworth, -- 1746-1825 -- Correspondence; Rice, Nathan, -- 1754-1829 -- Correspondence; Rivardi, John J. U. -- Correspondence; Schuyler, Philip John, -- 1733-1804 -- Correspondence; Sedgwick, Theodore, -- 1746-1813 -- Correspondence; Seton, William, -- 1746-1798 -- Correspondence; Smith, William Stephens, -- 1755-1816 -- Correspondence; Steuben, Friedrich Wilhelm Ludolf Gerhard Augustin, -- Baron von, -- 1730-1794 -- Correspondence; Swan, Caleb, -- -1809 -- Correspondence; Tousard, Louis de, -- 1749-1817 -- Correspondence; Troup, Robert, -- 1757-1832 -- Correspondence; Wadsworth, Jeremiah, -- 1743-1804 -- Correspondence; Washington, George, -- 1732-1799.; Washington, George, -- 1732-1799 -- Correspondence; Wilkinson, James, -- 1757-1825 -- Correspondence; Wolcott, Oliver, -- 1760-1833 -- Correspondence; Church family; Hamilton family; Schuyler family; Mint of the United States; New York (State). -- Supreme Court of Judicature; United States. -- Army. -- Office of the Inspector General; United States. -- Constitutional Convention -- (1787); United States. -- Continental Army; United States. -- Continental Congress; United States. -- Department of the Treasury; Society for Establishing Useful Manufactures; Finance, Public -- United States; Manufacturing industries -- United States; National banks (United States); Practice of law -- New York (State) -- New York; France -- Foreign relations -- United States; Great Britain -- Foreign relations -- United States; New York (State) -- Politics and government -- 1775-1865.; United States -- Economic conditions -- To 1865.; United States -- Foreign relations -- France; United States -- Foreign relations -- Great Britain; United States -- History -- Revolution, 1775-1783.; United States -- Politics and government -- 1783-1809.; McLane family; Army officers; Cabinet officers; Delegates, U.S. Continental Congress -- New York (State); Lawyers